Sofrimento (des)encarcerado : repercussões dos círculos de construção de paz na saúde mental de mulheres privadas de liberdade - Eleoterio, Alina Mourato (2024)
Introduction: Peacemaking Circles (PC) are restorative justice practices that create safe listening and speaking spaces designed to bring people together so that everyone is respected, have an equal opportunity to speak without being interrupted, and in which people get closer to each other's lives by sharing meaningful stories. The object of this research are the PC carried out with Women Deprived of Liberty (WDL) in the Female Penal Complex of Salvador BA, where the researcher works as a voluntary facilitator. Objective: the general objective is to analyze the repercussions of Peacebuilding Circles on the Mental Health of Women Deprived of Liberty. The specific objectives, in turn, are: a) Identify, in national and foreign literature, the existing conceptions about Mental Health and Mental Health Promotion; b) Understand the perception of Women Deprived of Liberty about the repercussions of PC on Mental Health; c) Investigate the interconnections between Integrative Practices and PC, analyzing whether these practices have the potential to emerge as a new Integrative and Complementary Practice. Methodology: qualitative approach, based on the Critical Phenomenology framework. To collect data, semi-structured interviews were carried out, with in-depth open questions and participant observation. The sampling was intentional, with nine women serving sentences in the closed regime of the Women's Penal Complex of Salvador being interviewed. The construction/closure of the sample was carried out through theoretical saturation sampling. The data were analyzed using the phenomenological-hermeneutic analysis model. From Results: data analysis it was possible to demonstrate that, on the one hand, imprisonment and social practices of inhumane treatment, medicalization and silencing of the inmates’ voice contribute to the process of undoing the world of Women Deprived of Freedom, on the other hand, the Peacemaking Circles help in the process of remaking the world of these women, as they have a cathartic and pedagogical effect, function as a space of resistance against abusive disciplinary power, generate abstraction from the prison reality and strengthen the hope of the inmates. Conclusions: The process of remaking the world has a direct impact on promotion of mental health, since Circles impact four personality dimensions related to the promotion of psychological well-being. First, in autonomy, due to the focus on an emancipatory vision regarding the objectives of the Circles. Secondly, in the positive relationship with others, as the pedagogical effect of the Circles contributes to improving the relationship between inmates. Third, in the dimension of self-acceptance, as the Circles make inmates feel good about themselves. And fourth, in the dimension called life purpose, as the strengthening of hope promoted by the Circles opens the future to post-incarceration possibilities, allowing them to believe that it is possible to find meaning in their own efforts and challenges. Regarding the potential of Circles to emerge as a new Integrative and Complementary Practice, it was initially demonstrated that PC can be considered healing practices of Traditional Medicine. Furthermore, the multiple approaches between PC and Group Integrative Practices were indicated, notably with Integrative Community Therapy. Considering these approaches and given the results achieved by the Circles in the context of mental health promotion, it is possible to conclude that they represent instruments with great potential to be used by professionals working in Mental Health field. However, for CCP to effectively emerge as a new integrative practice, it will initially be necessary to be disseminated in the health area and, after the massive use of these practices and the evaluation of the results achieved, a future inclusion of Circles could be considered of Peacemaking Circles in the National Policy of Integrative and Complementary Practices of the SUS (NPICP)